Arlindo Machado en Argentina: lecturas, impulsos y líneas de fuerza - Russo, Eduardo A. (2022)
This article outlines the impact of Arlindo Machado’s work on Argentina’s academic and cultural sphere from the translation of his texts into Spanish and his teaching and curatorial activities since the early 1990s. The lines of force of Machado’s itinerary are detected, with his recognized forays into the field o photographic creacion, his experiences in short films and multimedia works, his electronic books in differents architectures and formats, and the publications that have left notable marks, not only in Argentina, but also in other Latin American Countries.